Psychometric properties of the Satisfaction with life scale (SWLS) in a sample of individuals over the age of 40 years old from the Icelandic population - Anna Bára Unnarsdóttir 1993-; Kristín Hulda Gísladóttir 1994-; Róshildur Arna Ólafsdóttir 1994- (2018)
Background: The psychometric properties of different language versions of the Satisfaction with Life Scale (SWLS) has been shown to be good to excellent in general populations and clinical samples. The current study estimated the psychometric properties of the Icelandic version of the SWLS as well as general life satisfaction for a large, population based sample of Icelandic individuals over the age of 40. The current study is part of the largest scientific study to date conducted in Iceland, which evaluates the value of screening for a precursor of myeloma in Icelanders over the age of 40. Methods: All Icelandic individuals born preceding the year of 1976 (i.e., 40 years or older) were offered participation in a study screening for monoclonal gammopathy of undetermined significance (MGUS), which is a precursor to multiple myeloma. Individuals that provided informed consent were 78,581 and about half of those individuals completed at least one of the five self-report measures used in the current study. Results: The mean score on the SWLS was relatively high with females scoring slightly higher than males in most age groups. The relationship between satisfaction with life and age followed a nonlinear, slightly U-shaped curve, in which life satisfaction decreased until late middle age and then increased again. The SWLS had good internal consistency and construct validity in the current sample. Conclusions: The results of the current study were in accordance with previous studies into satisfaction with life. On average, the Icelandic population over the age of 40 reported being satisfied with their lives. Additionally, females reported being slightly more satisfied with their lives than males, and the relationship between life satisfaction and age was nonlinear and slightly U-shaped. Results from the current study indicate that the psychometric properties of the Icelandic version of the SWLS are good, and therefore, the Icelandic version of the scale is a reliable and valid measure of life satisfaction.